(5-w)(5w-4)=0

Simple and best practice solution for (5-w)(5w-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5-w)(5w-4)=0 equation:


Simplifying
(5 + -1w)(5w + -4) = 0

Reorder the terms:
(5 + -1w)(-4 + 5w) = 0

Multiply (5 + -1w) * (-4 + 5w)
(5(-4 + 5w) + -1w * (-4 + 5w)) = 0
((-4 * 5 + 5w * 5) + -1w * (-4 + 5w)) = 0
((-20 + 25w) + -1w * (-4 + 5w)) = 0
(-20 + 25w + (-4 * -1w + 5w * -1w)) = 0
(-20 + 25w + (4w + -5w2)) = 0

Combine like terms: 25w + 4w = 29w
(-20 + 29w + -5w2) = 0

Solving
-20 + 29w + -5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-5 + w)(4 + -5w) = 0

Subproblem 1

Set the factor '(-5 + w)' equal to zero and attempt to solve: Simplifying -5 + w = 0 Solving -5 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + w = 0 + 5 w = 0 + 5 Combine like terms: 0 + 5 = 5 w = 5 Simplifying w = 5

Subproblem 2

Set the factor '(4 + -5w)' equal to zero and attempt to solve: Simplifying 4 + -5w = 0 Solving 4 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5w = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5w = 0 + -4 -5w = 0 + -4 Combine like terms: 0 + -4 = -4 -5w = -4 Divide each side by '-5'. w = 0.8 Simplifying w = 0.8

Solution

w = {5, 0.8}

See similar equations:

| .9-.135= | | 15y+7= | | B+15=10 | | 7(3y-2)-6y= | | 4x-5+9x+37=110 | | x^5z^4/xz^3 | | e^1/2x=2 | | 3x^4-2x^2+(-6x^5)-7x=0 | | 2x*2+4x=0 | | 4=35-X | | -6-2+(-5)=0 | | X-3+1=5x-4x+1 | | 7b-80=4 | | X-.12x=300000000 | | 30+2X=60 | | x+50=40 | | 258=29x | | x-6=3x+8 | | -75=X-41 | | x-21=5x+3 | | -30+X=-42 | | 5x+1+8x-8=t | | k-3/7k=-6/7 | | -2x+20=2x+8 | | x^2-12x^2+45=0 | | x^2-11x-11x+121=0 | | x^2+3-4=6 | | 1/6x+5/7x=111 | | 7+Y=23 | | Log(2x-14)+log(x-2)=2 | | (6x-18y+27z)-(3xyz)= | | 9x^2-4x=-3 |

Equations solver categories